Spatially Resolved Transcriptomes of Mammalian Kidneys Illustrate the Molecular Complexity and Interactions of Functional Nephron Segments - Raghubar, Arti M.; Pham, Duy T.; Tan, Xiao; Grice, Laura F.; Crawford, Joanna; Lam, Pui Yeng; Andersen, Stacey B.; Yoon, Sohye; Teoh, Siok Min; Matigian, Nicholas A.; Stewart, Anne; Francis, Leo; et al. (Frontiers in Medicine, 2022)
Available transcriptomes of the mammalian kidney provide limited information on the spatial interplay between different functional nephron structures due to required dissociation of tissue with traditional transcriptomic based methodologies. A deeper understanding of the complexity of functional nephron structures requires a non-dissociative transcriptomics approach like spatial transcriptomics sequencing (ST-seq). We hypothesis that the application of ST-seq in normal mammalian kidneys will give transcriptomic insights within and across species of physiology at the functional structure level and cellular communication at cell level. Here, we applied ST-seq in six mouse and four human kidneys that were histologically absent of any overt pathology. We defined the location of specific nephron structures in the captured ST-seq datasets using three lines of evidence: pathologist’s annotation, marker gene expression and integration with public single-cell and/or single-nucleus RNA-sequencing datasets. We compared the mouse and human cortical kidney regions. In the human ST-seq datasets, we further investigated the cellular communication within glomeruli and regions of proximal tubules-peritubular capillaries by screening for co-expression of ligand-receptor gene pairs. Gene expression signatures of distinct nephron structures and microvascular regions were spatially resolved within the mouse and human ST-seq datasets. We identified 7,370 differentially expressed genes (padj <0.05) distinguishing species, suggesting changes in energy production and metabolism in mouse cortical regions relative to human kidneys. Hundreds of potential ligand-receptor interactions were identified within glomeruli and regions of proximal tubules-peritubular capillaries, including known and novel interactions relevant to kidney physiology. Our application of ST-seq to normal human and murine kidneys confirms current knowledge and localization of transcripts within the kidney. Furthermore, the generated ST-seq datasets provides a valuable resource for the kidney community that can be used to inform future research into this complex organ.